Aggregation of ZnO Nanocrystallites Using Polyol Process for Dye (Reactive Red) Sensitized Solar Cell. Issue 1 (January 2015) - Inamdar, Yusuf; Beedri, Niyamat; Kodam, Kisan; Shaikh, Arif; Pathan, Habib; Bhattacharya, Bhaskar
Summary In the present study, ZnO has been successfully synthesized using polyol mediated process at low temperature and doctor blade method was adopted for photoelectrode preparation. The ZnO samples possesses network of aggregated sphere like morphology having crystallite size around 15 nm. The surface morphology and crystal structure were characterized by using Scanning electron microscopy and X‐ray Diffraction, respectively. Dye Sensitized Solar Cells (DSSC) using ZnO photoanode is fabricated and characterized. The low cost organic textile dye (reactive red 141) used as a sensitizer in the fabrication of DSSC. The absorbance spectra of this dye have been investigated by UV‐visible spectrophotometry. Photovoltaic parameters such as short circuit current density Jsc, open circuit voltage Voc and Fill Factor were determined.